How much do rural Indian husbands care for the health of their wives′ - Singh Amarjeet; Arora Arvinder (Wolters Kluwer Medknow Publications, 2008)
Objective: To ascertain the response of husbands to their wives′ health problems. Materials and Methods: We selected 100 couples through a systematic random sampling from 4 purposively selected villages; these couples were interviewed by a social worker in rural North India through house-to-house survey. The role of husbands during pregnancy, puerperium and during the wives′ illness was explored. Their awareness with regard to the reproductive health problems of their wives was also ascertained. Another outpatient department (OPD)-based interview of female (n = 300) patients was conducted; 50 each at health post, subcenter, primary health centers (PHC), community health center (CHC), 50-bed hospital and apex institution. Previous consultation history was also obtained. Results: Husbands escorted their wives to hospital in 30-40% cases. This was mainly for a visit to bigger hospitals in cities/towns. Husbands decided regarding the treatment agency in the majority of cases. In 10% cases, they took time off their work during wives′ sickness and helped in household work. Consultation within a week was 100%. The husbands′ knowledge regarding the safe period was inadequate. Majority (78%) said that women remained ill more often. Most wives were satisfied with the role of their husbands during their pregnancy or illness. A majority (80%) of husbands favored education of women up to the 10th standard and 87% were in favor of working women. Conclusion: Reasonably favorable attitude of husbands towards their wives′ health problems was witnessed. This needs to the carefully nurtured.